Iron-entrapped niosomes and their potential application for yogurt fortification. (December 2016) - Gutiérrez, G.; Matos, M.; Barrero, P.; Pando, D.; Iglesias, O.; Pazos, C.
Abstract: Several formulations were tested for iron-entrapped niosomes with high stability and encapsulation efficiency. A modified ethanol injection method was selected for niosomes preparation. Niosomes formulated with Glycerol monooleate, Polyglyceryl-3 dioleate or Sorbitan monooleate as food-grade surfactants and dodecanol as membrane stabilizer showed iron encapsulation efficiencies in the 72–84% range. Niosomes stability against simulated gastric fluid and simulated intestinal fluid was evaluated by measuring the entrapment efficiency and oxidation of iron. The best formulations were selected for preparation of iron-fortified yogurts. Sensory, rheological and stability properties of the control yogurt were only slightly affected by iron-entrapped niosomes. These results demonstrated that yogurt could be a suitable vehicle for the iron-entrapped niosomes formulated in this work. Highlights: Stable food-grade niosomes with 72–84% of encapsulated iron were prepared. Iron release from niosomes occurred in a simulated gastric fluid. Iron oxidation inside niosomes took place in a simulated intestinal fluid. Some yogurt physical properties were slightly affected by Fe-entrapped niosomes.